ITRAQ‐based quantitative proteomics reveals biomarkers/pathways in psoriasis that can predict the efficacy of methotrexate. (24th June 2022) - Yan, K.X.; Meng, Q.; He, H.; Zhu, H.W.; Wang, Z.C.; Han, L.; Huang, Q.; Zhang, Z.H.; Yawalkar, N.; Zhou, H.; Xu, J.X.
Abstract: Background: Methotrexate (MTX) is the first‐line medicine to treat psoriasis. So far, there has been less research on protein biomarkers to predict its efficacy by the proteomic technique. Objectives: To evaluate differentially expressed proteins in peripheral mononuclear cells (PBMCs) between good responders (GRs) and non‐responders (NRs) after MTX treatment, compared with normal controls (NCs). Methods: We quantified protein expression of PBMCs with four GRs and four NRs to MTX and four NCs by isobaric tags for relative and absolute quantification (iTRAQ), analysing and identifying proteins related to efficacy of MTX in 18 psoriatic patients. Results: A total of 3177 proteins had quantitative information, and 403 differentially expressed proteins (fold change ≥1.2, P  < 0.05) were identified. Compared to NCs, upregulated proteins (ANXA6, RPS27A, EZR, XRCC6), participating in the activation of NF‐κB, the JAK–STAT pathway and neutrophil degranulation were detected in GRs. The proteins (GPV, FN1, STOM), involving platelet activation, signalling and aggregation as well as neutrophil degranulation were significantly downregulated in GRs. These proteins returned to normal levels after MTX treatment. Furthermore, Western blotting identified the expression of ANXA6 and STAT1 in PBMCs, which were significantly downregulated in GRs, but not in NRs. Conclusions: We identified seven differentially expressed and regulated proteins (ANXA6, GPV, FN1, XRCC6, STOM, RPS27A and EZR) as biomarkers to predict MTX efficacy in NF‐κB signalling, JAK–STAT pathways, neutrophil degranulation, platelet activation, signalling and aggregation.